2021
DOI: 10.52547/jad.2021.3.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Annotated checklist of the snakes of Bengaluru Urban District, Karnataka, India with notes on their natural history, distribution, and population trends over the last 150 years

Abstract: Systematic and thorough studies of snake populations across large areas are rare in the tropics. Bengaluru city in southern India has not had a thorough checklist of snakes in over a century, during which time land-use changes, taxonomic revisions, and fluctuating reptile populations have left the current status of snakes of this region unclear. We combine data from snake rescues, visual encounter surveys, and other reliable records to generate a contemporary checklist of 33 snake species (15 of which are nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Elapids are in fact considered to have a high WR in which larger individuals forage on a variety of prey animals and occasionally consume snakes that exceed their own mass (Greene, 1983; Shine and Wall, 2007). Snake species that are commonly associated with human-dominated environments (Barhadiya and Ghosh, 2021; Kalki et al, 2021) showed a high relative importance in the diet of N. naja ( N. naja , 31%; Daboia russelii , 23.8%; and Ptyas mucosa , 11.9%). Whether the high proportion of ophiophagy results from actual preference or simply from N. naja feeding more often on particularly common animals in an urban environment remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Elapids are in fact considered to have a high WR in which larger individuals forage on a variety of prey animals and occasionally consume snakes that exceed their own mass (Greene, 1983; Shine and Wall, 2007). Snake species that are commonly associated with human-dominated environments (Barhadiya and Ghosh, 2021; Kalki et al, 2021) showed a high relative importance in the diet of N. naja ( N. naja , 31%; Daboia russelii , 23.8%; and Ptyas mucosa , 11.9%). Whether the high proportion of ophiophagy results from actual preference or simply from N. naja feeding more often on particularly common animals in an urban environment remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the Indian species (B. beddomei, B. dightoni, B. flaviviridis, B. forsteni, B. nuchalis, B. thackerayi, B. trigonata) are known from the Western Ghats (Narayanan et al 2023), but only two (B. flaviviridis and B. forsteni) have been recorded in forested areas of both the Eastern and Western Ghats (Ganesh et al 2020a). The Yellow-green Catsnake (Boiga flaviviridis) was originally described from Berhampur, Odisha, India, and has subsequently been recorded from forested regions across much of peninsular India (Vogel and Ganesh 2013;Dharmendra et al 2016;Sharma et al 2016;Choure et al 2021;Kalki et al 2021; Fig. 1).…”
mentioning
confidence: 99%